Endovascular stroke therapy in Austria: a nationwide 1‐year experience. (3rd February 2016) - Serles, W.; Gattringer, T.; Mutzenbach, S.; Seyfang, L.; Trenkler, J.; Killer‐Oberpfalzer, M.; Deutschmann, H.; Niederkorn, K.; Wolf, F.; Gruber, A.; Hausegger, K.; Weber, J.; et al.
Abstract : Background and purpose: Based on a tight network of stroke units (SUs) and interventional centres, endovascular treatment of acute major intracranial vessel occlusion has been widely implemented in Austria. Documentation of all patients in the nationwide SU registry has thereby become mandatory. Methods: Demographic, clinical and interventional characteristics of patients who underwent endovascular treatment for acute ischaemic stroke in 11 Austrian interventional centres between 1 October 2013 and 30 September 2014 were analysed. Results: In total, 301 patients (50.5% women; median age 70.5 years; median National Institutes of Health Stroke Scale score 17) were identified.193 patients (64.1%) additionally received intravenous thrombolysis. The most frequent vessel occlusion sites were the M1 segment of the middle cerebral artery ( n = 161, 53.5%), the intracranial internal carotid artery ( n = 60, 19.9%) and the basilar artery ( n = 40, 13.3%). Stent retrievers were used in 235 patients (78.1%) and adequate reperfusion (modified Thrombolysis in Cerebral Infarction scores 2b and 3, median onset to reperfusion time 254 min) was achieved in 242 patients (81.4%). Symptomatic intracranial haemorrhage occurred in 7%. 43.8% of patients ( n = 132) had good functional outcome (modified Rankin Scale score 0–2) and the mortality rate was 20.9% ( n = 63) after 3 months. Compared to the anterior circulation, vertebrobasilar stroke patients had higher mortality. Patients with secondary hospital transportation had better outcomes after 3 months than in‐house treated patients. Conclusion: Our results document nationwide favourable outcome and safety rates of endovascular stroke treatment comparable to recent randomized trials. The ability to provide such data and the need to further optimize such an approach also underscore the contribution of respective registries.